RESPONSIBLE RESEARCH AND INNOVATION (RRI) IN HUNGARY: A WESTERN MODEL, AN EASTERN ILLIBERAL REGIME, AND A CASE OF DEFERRED INSTITUTIONAL ADAPTATION - Varju, Marton (Pravni zapisi, 2021)
Responsible research and innovation (RRI) is a mode of research, development and innovation (RDI) governance which has proliferated primarily in European states with a tradition and/or culture of participatory and deliberative technology governance. It assumes the existence of open, transparent and accessible policy-making processes, and a culture of responsibility and accountability in government and in the private domain. In Hungary, where RDI is supposed to be the key to economic competitiveness, RRI has never taken root. Examining the regulation of the Hungarian RDI system, it becomes clear that there is a significant degree of institutional incompatibility with the solutions promoted by RRI. More significantly, the contemporary system of government and administration and the prevailing model of policy-making and governance prevent or exclude deliberately the implementation of RRI.